Adductor Tendon Repair: Case Report and Description of a Novel Approach for Improved Exposure. Issue 1 (17th March 2021) - Gerhardt, Michael; Sherman, Benjamin; Trentacosta, Natasha; Hobart, Sarah; Hutchinson, William; Chahla, Jorge
Abstract : Groin pain is one of the most common and challenging diagnoses for a sports medicine physician. Up to 64% of groin injuries involve the adductor tendons, which can be very difficult to treat with or without surgical intervention. The purpose of this article is to report the 2-year outcomes of a patient that presented with an acute proximal adductor tendon injury and to describe a novel surgical approach. This is a case of a 36-year-old elite athlete that presented with an acute adductor longus tear. The patient was treated with surgical repair using a parainguinal approach and bioabsorbable suture anchors into the adductor longus anatomic footprint. The patient had a full return to sport at 8 weeks postoperatively. At 2 years the patient was symptom free and still participating in the same elite level of sport. Adductor repair using a parainguinal approach and bioabsorbable suture anchors is a viable surgical option for patients in the acute setting.